KONTRIBUSI BAHASA ARAB TERHADAP BAHASA INDONESIA - Rusdin Rusdin (State Institute of Islamic Studies (IAIN) Palu, 2005)
The development of a language is not free from the influences of other languages. For example, as an official language, Indonesian language used by Indonesians, is not free from the influences of other languages, either local languages such as Javanese language and Sundaness language or foreign ones such as English and Arabic.It is within this context that this article aims at discussing contribution of Arabic to the development of Indonesian language.